PENGGUNAAN GYPSUM BLOCK UNTUK MENGUKUR KADAR AIR PADA TANAH LEMPUNG - Sir, Tri M.W.; Bolla, Margareth E.; Nesnay, Danial (Jurnal Teknik Sipil, 2012)
The test of soil moisture content that most often method applied is gravimetric. By the development of sciences, nowdays a sensor device test on soil moisture content that is called gypsum block. Such devices could be directed inplanted in the place where the moisture content would be measured. This research aimed at getting the calibration equation and correlation coefficient of gypsum block and to determine whethergypsum block could be used as a test of moisture content of clay. The kind of sample was taken from Oebelo village, Central Kupang Subdistrict, East Nusa Tenggara and variations of water used were 15%, 20%, 30.7% and 40%, and total samples were 20. The results of the research revealed that calibration equation of gypsum block to the measurements for 7 days (constant resistantion) was Y=1.323x-0.54 by r = 0.835. The results of field testing and compared with gravimetric method obtained difference moisture content value in the range of 0.26%-2.56%. From the results it could be concluded that the gypsum block could be used as a device to measure the moisture content of clay.